Review: Pemanfaatan Teknik Penginderaan Jauh untuk Menentukan Daerah Potensi Penangkapan Ikan di Perairan Laut - Mirna Ria Andini; Murhaban Murhaban (LPPM STIKes SITI HAJAR dan Insight Power, 2021)
Researchers in various international programs have studied the potential use of remote sensing data to obtain accurate information about an object, area, or phenomenon through the analysis of data acquired by a device that not in contact with it. Remote sensing technology can be used in mapping the potential fishing ground with the important oceanography parameters. The aims of this research are determined the potential fishing ground in Aceh sea waters use oceanography parameters with utilization Aqua and Terra MODIS data images satellite. The methods used in this research are Algorithm Theoretical Basis Document 25 (ATBD 25) and ATBD 19 to images correlation. This study introduced a system to merge two different data image satellite obtained from Aqua and Terra MODIS and data in-situ. The remote sensing technique for retrieving ocean environmental parameters of the potential fishing ground is proposed and is primarily apply to analyze the relationship between data oceanographic, data in-situ, and CPUE of fishing ground in Aceh sea waters.Keywords: Remote Sensing, Fishing Ground, Images Satellite, Aqua Terra MODIS